Experiences of international medical students enrolled in Chinese medical institutions towards online teaching during the COVID-19 pandemic - Aslam, Sarfraz; Akram, Huma; Saleem, Atif; Zhang, BaoHui (PeerJ, 2021)
Introduction . The COVID-19 pandemic has forced the world to pause. One hundred and eighty-eight countries have imposed countrywide school closures, affecting more than 1.5 billion children and youths. The majority of academic leaders are currently encouraging online education to resolve this crisis. This study aimed to investigate international medical students’ (IMS) experiences of online teaching during the COVID-19 pandemic. Methods Data were collected online using a validated questionnaire and one open-ended question, presented on the Google forms platform. The study attracted responses from 1,107 IMS volunteer participants. IBM SPSS v. 25, GraphPad Prism v. 9, and MindManager v. 2018 were used for data analysis. All variables were subjected to descriptive statistical analysis. The Mann–Whitney U test was used in subgroup analysis and the Kruskal-Wallis test was also applied for year-wise comparisons. Open-ended text responses were analyzed qualitatively, extracting themes by which responses were classified. Results Among 1,107 respondents, a total of 67.8% were males, and the majority (63.1%) of the IMS were in the age group of 21–23 years. The results show that more than half of the respondents reported their Internet connection quality as poor to average. Poor Internet connection severely affected IMS online learning experience. Persistent and recurrent issues with Internet access became a significant concern for IMS. Lack of electricity is one of the factors that can contribute to poor learning output and dissatisfaction with online teaching. IMS perceive online medical education as unhelpful in several phases of the training, such as improving their clinical skills, knowledge, and discussion skills. Conclusions During these unprecedented periods, online teaching has allowed medical education to continue. However, IMS are generally dissatisfied with online teaching. Medical students must visualize the human body, so supportive technologies are important to compensate for the lack of clinical practices. Medical institutions may need to invest in faculty training programs and continually adjust to enhance the content of online training and international partnerships. A switch from conventional face-to-face teaching to a fully functional virtual education framework in the medical education field will take time and experience.
Keywords: Medical students; Medical education; COVID-19; Online teaching; China; Pandemic; International students